2009
DOI: 10.1002/elan.200804596
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Electrochemically Deposited Nanocomposite Film of CS‐Fc/MWNTs/GOD for Glucose Biosensor Application

Abstract: A simple and controllable electrodeposition approach was proposed for one-step construction of glucose biosensors by in situ co-deposition of ferrocene-branched chitosan derivatives (CS-Fc), multiwalled carbon nanotubes (MWNTs), and glucose oxidase (GOD) onto electrode surface. The formation of CS-Fc could not only effectively prevent the leakage of Fc and retain its electrochemical activity, but also provide a biocompatible microenvironment for retaining the native activity of the immobilized biomolecules. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The background current of the CS-Fc modified electrode was greater than that of bare electrode owing to the resistance and double layer capacitance caused by CS. In the composite film of CSFc/MWCNTs, the reduction and oxidation peak currents increased greatly (curve c), which was consistent with our previously result [28]. The reason could be due to the increased electrochemical active Fc in the CS films electronically bridged by MWCNTs.…”
Section: Cyclic Voltammetric Characterization Of the Modified Electrodesupporting
confidence: 90%
See 2 more Smart Citations
“…The background current of the CS-Fc modified electrode was greater than that of bare electrode owing to the resistance and double layer capacitance caused by CS. In the composite film of CSFc/MWCNTs, the reduction and oxidation peak currents increased greatly (curve c), which was consistent with our previously result [28]. The reason could be due to the increased electrochemical active Fc in the CS films electronically bridged by MWCNTs.…”
Section: Cyclic Voltammetric Characterization Of the Modified Electrodesupporting
confidence: 90%
“…This strategy can not only effectively prevent leakage of Fc from the matrix and remain the biocompatibility of CS, but also combine redox activity and biocompatibility to the novel formed composite [26,27]. Our research demonstrated that further introduction of multiwalled carbon nanotubes (MWCNTs) to the CS-Fc composite would effectively improve the conductive property, facilitate the electron-transfer and enhance the effective electroactive surface area of the resulted film [28], making CS-Fc/ MWCNTs composite an attractive candidate for constructing stable and sensitive immunosensors. In addition, the abundant amino groups in CS could offer great active sites for further Au NPs assembling, and thus, the Au NPs modified electrodes have very large surface area, are simple to fabricate and functionalize, retain metallic conductivity, and lend themselves to facile biomolecule attachment [29,30].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…These studies demonstrated that deposition conditions could be developed to be sufficiently mild to preserve the protein's catalytic function. Subsequently, a large number of studies have extended this work for the co-deposition of various proteins [93][94][95][96][97][98][99][100][101][102][103][104][105][106] and many of these studies have been described in a recent review on the use of chitosan for electrochemical biosensing [8]. In addition to proteins, it is also possible to co-deposit various other materials for incorporation into the electrodeposited chitosan film [68,[107][108][109][110][111].…”
Section: Co-depositionmentioning
confidence: 97%
“…K m can be calculated by the slope and the intercept of the plot in Fig. 7 ) [56]. The lower magnitude of K m confirms the retention of GOx native structure in GCE/NS-C/GOx/ nafion, which results in higher affinity and activity of the GOx to the glucose in an enzymatic reaction.…”
Section: Electrochemical Behavior Of the Modified Electrodementioning
confidence: 80%